Electrochemical Detection of Melamine - Xue, J; Lee, P; Compton, R (Wiley, 2014)
Poly(caffeic acid) polymer was immobilized onto the surface of a glassy carbon electrode via electropolymerization. Voltammetry shows a signal related to the two-electron oxidation of the immobilized hydroquinone groups in the caffeic acid monomer units. The modified electrode in aqueous solution shows complexation of the electrogenerated o-quinone species with melamine thus allowing in the electrochemical detection of melamine by recording the shift in potential of the oxidation signal of the polymer. Melamine detection was investigated in pure aqueous solutions and in the presence of milk powder solutions and the proposed analytical method of melamine detection in milk powder was applied successfully with an average recovery of ca. (91±7.9)%. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.